Ineffective hand washing and the contamination of carrots after using a field latrine. (7th March 2016) - Monaghan, J.M.; Hutchison, M.L.
Abstract: A study was undertaken to simulate the likely effects of a field worker with poor hygienic practices that had returned to work too soon after recovering from an infection by an enteric pathogen. The studies simulated a variety of hand‐washing practices from no washing to washing with soap and water followed by an application of alcohol gel after using a field latrine. The numbers of generic Escherichia coli isolated from workers' hands declined with increasing thoroughness of hand‐washing treatments with unwashed hands > water > water and soap > water, soap and alcohol gel. Where gloves were worn the counts obtained for the treatments were significantly reduced, but it was observed that unwashed hands contaminated gloves during the process of putting them on. Hand contamination following the use of a field latrine transferred contamination to carrots. These results suggest that if no gloves are worn it would be best practice to wash hands with water and soap and apply alcohol gel after using a field latrine. Wearing gloves reduced the risk of contaminating handled produce but workers should still wash their hands after using a field latrine before applying gloves. Significance and Impact of the Study: This study shows that inadequate hand hygiene in the field following the use of a field latrine can transfer bacterial contamination to hand‐harvested carrots. Where fresh produce crops are to be handled by workers, wearing gloves reduces the risk of contaminating produce but workers should still wash their hands after using a field latrine before applying gloves. If no gloves are worn it would be best practice to wash hands with water and soap and apply alcohol gel after using a field latrine. Abstract : Significance and Impact of the Study: This study shows that inadequate hand hygiene in the field following the use of a field latrine can transfer bacterial contamination to hand‐harvested carrots. Where fresh produce crops are to be handled by workers, wearing gloves reduces the risk of contaminating produce but workers should still wash their hands after using a field latrine before applying gloves. If no gloves are worn it would be best practice to wash hands with water and soap and apply alcohol gel after using a field latrine.